DEVELOPMENT OF WEB-BASED SERVICEAPP APPLICATIONS AND USABILITY TESTING USING THE USABILITY SCALE SYSTEM (SUS) CASE STUDY: PT TELEMEDIA MITRA ERAJAYA - Lukito, Axcel; Wiratama, Jansen; Santoso, Hari (Faculty of Information Technology, Universitas Tarumanagara, 2022)
Today, many companies have taken advantage of the use of technology to help their business processes. One of Indonesia's companies engaged in Test and Measurement, Network Monitoring and Telecom Professional Services is PT Telemedia Mitra Erajaya which uses applications to help its business processes, especially in inventory. This study aims to evaluate and produce a recommended application design based on the evaluation results using the System Usability Scale (SUS) method to measure application usability. In usability testing, there are five components: Learnability, Efficiency, Memorability, Errors, and Satisfaction. After the Usability evaluation is complete, the results will be used as recommendations for the design of the Serviceapp application. The results of usability testing on existing enterprise applications get the results of 54.75 points. The framework for designing the Serviceapp application is Laravel with the adminLTE template. This research results from a website-based Serviceapp Inventory application that can help companies enter data and are easy to access. The usability testing results obtained are 74.75 points. With the new application, test results increased by 20 points.